1984
DOI: 10.1177/155005948401500107
|View full text |Cite
|
Sign up to set email alerts
|

Familial Photosensitive Epilepsy: Effectiveness of Clonazepam

Abstract: We describe the clinical features of a family with photosensitive epilepsy, followed for 13 years. Generalized paroxysmal discharges induced by photic stimulation appeared in all 9 siblings. Generalized seizures, myoclonic jerks, and absences appeared in variable combination in 7 of them who on clonazepam remained free from seizures for a seven-year follow-up period. On EEG the paroxysmal abnormalities induced by photic stimulation abated during clonazepam medication.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2004
2004
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 20 publications
0
5
0
Order By: Relevance
“…VPA was recommended for children with idiopathic generalized epilepsy (68), but those with seizures only during video games perhaps do not require AEDs. Benzodiazepines, particularly clonazepam (151), also have been found to be effective. A young boy with Lennox–Gastaut syndrome and pattern‐sensitive seizures was responsive to bromocriptine, 5 mg tid (152).…”
Section: Medicationsmentioning
confidence: 99%
“…VPA was recommended for children with idiopathic generalized epilepsy (68), but those with seizures only during video games perhaps do not require AEDs. Benzodiazepines, particularly clonazepam (151), also have been found to be effective. A young boy with Lennox–Gastaut syndrome and pattern‐sensitive seizures was responsive to bromocriptine, 5 mg tid (152).…”
Section: Medicationsmentioning
confidence: 99%
“… 109 Benzodiazepines, particularly clonazepam, are effective in myoclonic jerks, and ethosuximide is effective in absence seizures. 44 Lamotrigine and carbamazepine may be effective in treatment but may increase jerks. 35 , 61 Psychiatric support is also needed for self-induced seizures.…”
Section: Introductionmentioning
confidence: 99%
“…AEDs that have been used in PSE with variable results in small trials include clonazepam (CZP) (5), lamotrigine (LTG) (6), levetiracetam (LEV) (7), and vigabatrin (VGB (8). In the largest trial to date, Harding and Jeavons (9) found that photosensitivity was abolished by sodium VPA in 40 of 65 patients.…”
Section: Discussionmentioning
confidence: 99%